Counseling on Adolescent Reproductive Health and Early Marriage at SMPN 2 Kroya, Indramayu Regency - Dini Nurfajri Hayati; Dian Zahra N; Sabiq Rizki Hasan; Hasanudin (Kawakib: Journal of Multidisciplinary Research, 2025)
This article focuses on reproductive health education and prevention of early marriage among adolescents, especially 9th grade junior high school students. Given the high rate of early marriage that has a negative impact on the health and future of adolescents, this program aims to increase adolescent knowledge about the importance of reproductive health and the risks associated with early marriage. Adolescence is a phase of human development that occurs between childhood and adulthood, usually ranging from 10 to 19 years of age. However, this age limit can vary depending on cultural and social contexts. Characteristics of adolescents such as Physical Development, Adolescents experience significant physical growth, including hormonal changes that affect body growth, sexual development, and appearance. Cognitive Development In this phase, adolescents begin to develop the ability to think abstractly, make decisions, and understand the consequences of their actions. They also begin to form self-identity and personal values. Emotional Development: Adolescents often experience emotional fluctuations and search for identity. They may face pressure from peers and the social environment, which can affect their mental health. Social Development: Adolescents begin to form more complex relationships with peers, family, and the community. They learn about social interactions, responsibilities, and roles in the community. Sometimes teenagers also Teenagers often face various challenges, including pressure to excel in school, mental health problems, promiscuity, and the risk of risky behavior such as drug use and premarital sex. Until early marriage occurs, Early marriage is a marriage that occurs to individuals who are still under the legal age for marriage, which is usually determined by law in each country. In many places, early marriage often occurs in teenage girls under the age of 18. so to reduce the risk of early marriage we as students provide counseling on this matter. Counseling activities are carried out using interactive methods involving presentations, discussions, and the use of visual media such as power points, videos, and images to facilitate understanding of abstract concepts. The results of the activity showed that the participants were very enthusiastic, with many questions asked and a significant increase in knowledge after participating in the counseling. However, there were several obstacles faced, such as the lack of focus of some participants which may be caused by individual factors and environmental conditions. This program is expected to have a positive impact on efforts to prevent early marriage and increase adolescent awareness of reproductive health. In addition, this report also includes details of the budget and implementing team involved in the activity, as well as recommendations for future program development.